Rotor Angle Analysis on Power Proportion in Generator and Photovoltaic Hybrid Low Voltage System - Fredi Prastiyo; Mochammad Facta; Susatyo Handoko (Jurnal Teknik Elektro, 2024)
Electrical energy is essential in modern society, and with the growing demand, all available energy resources are being utilized to meet this need. Insufficient planning and calculation in energy provision can affect the stability of electricity generated by power plants, especially in low-voltage microsystems directly connected to loads. This study investigates the behavior of synchronous microgenerators and photovoltaic systems, focusing on the rotor angle of the generator. Changes in the photovoltaic contribution can cause shifts in the generator's rotor angle, necessitating an analysis of these shifts. An experimental method was used to measure and analyze the power distribution by recording current and voltage in a micro synchronous generator and a grid-tie inverter under a 300-watt linear load. The results show that the generator’s rotor angle remains stable and the grid-tie inverter remains synchronized, with an average angle of 40.2° at a photovoltaic contribution of 32.26% and a synchronous microgenerator contribution of 67.74%. However, when the photovoltaic supply exceeds 37.00%, the rotor angle shifts further, leading to a loss of synchronization in the grid-tie inverter. Additionally, irradiance was found to have a linear effect on photovoltaic distribution. The findings of this study contribute to a better understanding of rotor angle behavior and grid synchronization, providing insights for the development of more reliable and efficient renewable energy systems that maintain electrical stability in low-voltage applications.